Policy Enactment During a Pandemic: How One School Responded to COVID-19 in Negotiation With a Nonprofit Partner. (February 2022) - Dorner, Lisa M.; Harris, Kelly; Willoughby, Blake
Policymaking is not linear or neutral, nor is it ever made or enacted in isolation, especially not during a crisis. Framed by theories on the contextual, interactive nature of policy enactment, this year-long, ethnographic study examined how an urban elementary school and nonprofit organization worked to address challenges made visible by the COVID-19 pandemic. Analyses explored how negotiations among the school, its nonprofit partner, and district shaped pandemic policy responses. Data included 35 transcriptions and eight field notes from stakeholder interviews and principal–partner meetings, and 128 external stakeholder artifacts. Findings showcase the policy enactment of family–school communication and access to remote learning, and limitations of the partnership due to structural and racialized processes. The discussion presents implications for educational policymaking in response to crises, highlighting the need to understand the external contexts and racialized discourses that are part of shaping those responses to be dynamic and "nonlinear."